ANALISIS PENERAPAN SISTEM INFORMASI PEMERITAH DAERAH (SIPD) PADA BIDANG PERBENDAHARAAN DAERAH BPKPAD KABUPATEN PURWOREJO - Khafida, Rosiana; Fatimah, Ari Nurul (Mount Hope Economic Global Journal, 2025)
The Regional Government Information System (SIPD) is an information system developed by the Ministry of Home Affairs to support the integrated processes of planning, budgeting, implementation, and financial reporting of local governments, as regulated in Minister of Home Affairs Regulation Number 70 of 2019 concerning the Regional Government Information System. This study aims to analyze the implementation of SIPD in the Regional Treasury Division of BPKPAD Purworejo Regency. The research method used is a qualitative descriptive approach with data collection techniques through observation, interviews, and documentation studies. The results show that the implementation of SIPD has brought positive impacts on the efficiency of regional financial management. However, there are still several challenges, such as technical system disruptions, limited human resources, and the need for internal work structure improvements. Based on these findings, enhancement strategies need to be implemented to ensure optimal execution of SIPD.